Grice subtalar arthrodesis of bilateral adult flatfoot in a professional dancer: a case report - Pedrazzini, Alessio; Bastia, Paolo; Bertoni, Nicola; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Adult acquired flatfoot deformity (AAFD) is a common pathology and an important cause of pain and disability. This deformity causes a progressive flattening of the foot arch which has traditionally been associated with posterior tibialis tendon (PTT) dysfunction. Operative treatment is indicated after the failure of conservative management aiming to achieve proper alignment of the hindfoot and to maintain as much flexibility as possible. If subtalar osteoarthritis is present, subtalar arthrodesis is usually the best therapeutic option. Grice-Green subtalar arthrodesis is a widely used procedure.Methods: This report describes a case of bilateral painful AAFD in a 39-years old female professional dancer treated with Grice-Green subtalar arthrodesis with an autologous corticocancellous graft harvested from the ipsilateral proximal tibia. Surgeries were performed 3 years apart from each other.Results: The patient followed had good clinical and radiological outcomes. She returned to dance 4 months after surgery with no referred pain or limitations. Conclusions: Due to its versatility and capability to restore the shape and thickness of the hindfoot Grice-Green procedure is a simple and effective technique for the treatment of AAFD with subtalar osteoarthritis and a valid option to solve professional disabilities as it happened in this case with a professional dancer.